The USA’s Shale Oil Revolution: OPEC Strategies and Oil Prices War in Global Economy - Saputra, Cahya Handy; Prakoso, Andria Luhur (Interdisciplinary Social Studies, 2022)
Background: At the beginning of 2020, the Covid-19 pandemic attacked the world and affected the continuity of the world economy. This condition also causes oil prices to decline further. OPEC plans a strategy to realize its role as a regulator of the world oil trade. Not only the global economy but the stock market is also affected by the decline in oil prices. Production of shale oil in the United States lowered OPEC oil prices, coupled with economic conditions during the Covid-19 pandemic which worsened the international economy. Aim: The authors examined changes in oil prices due to United States’ shale oil. Method: The qualitative method and literature review were employed in this study. The information was compiled from a variety of documents and other sources. Findings: The United States reduced its reliance on OPEC imports, which resulted in lower OPEC oil prices due to an oversupply and decreasing demand. Along with the Covid-19 epidemic, not only is the global economic collapse growing worse, but the decrease in oil prices in early 2020 is getting worse as well. Finally, the world economy suffered a downturn, which impacted the international capital market.